Reenactment Practices to young learners in teaching English - Syamsiah Depalina Siregar; Pipit Rahayu (English Language Teaching and Research, 2018)
English is interested by the young learners. They are fun when learning English. It is proved by many young learners follows our free courses in a village. It is located in Sarogodung Village, Sipirok, South tapanuli, North Sumatera. They do not receive English in their formal education. That is the reason of writer gave free courses for them. The aims of this article is to tell that the using appropriate method in learning English be key point approach for the young learners. English can be lovely subject for them. The method used in this article is Reenactment. It is a model reacted from the story. It can be as overt simulation. It used to suggest the young learners’ motivation in learning English. The method of the article is descriptive analysis. The sample is young learners consists of 25 people. They come from 7 up to 10 years old. The writer used interview, observation and test to get the data. The result of the article was the young learner enthusiast, full spirit, enjoy in learning English. They do not felt that English is bored. It depends on the suitable method and strategies in teaching and learning the English. Key word: Reenactment, young leaner, teaching method